Efficacy of telehealth acceptance and commitment therapy for weight loss: a pilot randomized clinical trial. Issue 8 (31st March 2021) - Bricker, Jonathan B; Mull, Kristin E; Sullivan, Brianna M; Forman, Evan M
Abstract: Telehealth coaching for weight loss has high population-level reach but limited efficacy. To potentially improve on this limitation, the purpose of this study was to determine the preliminary efficacy of the first known telephone coaching acceptance and commitment therapy (ACT) intervention for weight loss. A two-arm, stratified, individually randomized pilot trial comparing ACT ( n = 53) with standard behavioral therapy (SBT; n = 52) was used for this study. Both interventions were delivered in 25 telephone coaching calls (15–20 min each) over a 12 month period. Weight was measured at baseline and 3, 6, and 12 month postrandomization follow-ups. Recruited from 32 U.S. states, participants were of mean age 40.7, 42% male, 34% racial/ethnic minority, and mean baseline body mass index of 34.3. Fractions of 10% or more scale-reported weight loss: 15% for ACT versus 4% for SBT at 3 month follow-up ( N = 86; odds ratio [OR] = 4.61; 95% confidence interval [CI]: 0.79, 26.83), 24% for ACT versus 13% for SBT at 6 month follow-up ( N = 72; OR = 2.45; 95% CI: 0.65, 9.23), 30% for ACT versus 30% for SBT at 12 month follow-up ( N = 57; OR = 0.93; 95% CI: 0.28, 3.09). Fractions of 10% or more self-reported weight loss at 12 month follow-up: 25% for ACT versus 15% for SBT ( N = 75; OR = 2.38; 95% CI: 0.68, 8.34). The conclusion of the study was the preliminary evidence that telephone coaching ACT may be efficacious for weight loss. Lay Summary: Telephone coaching for weight loss reaches many people but has achieved very limited levels of weight loss. A program called acceptance and commitment therapy (ACT) is promising as an in-person weight loss program. However, ACT had not been tested before as a telephone coaching program. We conducted a 1 year telephone coaching study of 105 adults with overweight/obesity comparing ACT with standard behavioral therapy (SBT) coaching. The results showed that ACT telephone coaching had very encouraging levels of weight loss success compared to (SBT) coaching. These results suggest that telephone coaching ACT may be useful for weight loss.